Tuberculin Skin Test Reactivity is Dependent on Host Genetic Background in Colombian Tuberculosis Household Contacts (2012)
ABSTRACT: The tuberculin skin test (TST) measures the intensity of antimycobacterial acquired immunity and is used to diagnose latent infection with Mycobacterium tuberculosis. We report evidence for a codominant gene explaining 65% of the TST variability. Disregarding the host genetic background may lead to misclassifications of TST-based diagnosis of latent M. tuberculosis infection.